The Incidence of Bleeding and the Factors That Influence Its Development among Patients Admitted With Dengue Fever - Thapa, Krishna Bahadur; KC, Namrata; Koirala, T; Bhatttarai, A (Journal of Gandaki Medical College-Nepal, 2017)
Background: Dengue virus is now classified as a major global health threat by the World Health Organization. Bleeding is a common complication and is one of the most feared. There is an increase incidence in the adult population, hence, the focus of this study. Objectives: To determine the incidence of bleeding and the factors that influence its development among patients admitted with dengue fever at Fatima Medical Center, Phillipines from January 2009 to December 2011. Methods: This is a case control study using chart review. The incidence of bleeding is calculated using risk ratio. Factors affecting bleeding are determined using chi square for qualitative variables and T-test or ANOVA for quantitative variables. Simultaneous determination of factors association with bleeding will be analyzed using multiple logistic regression. Level of significance will be set at alpha = 0.05. Results: The female sex is significantly more prone to develop bleeding (p=0.044). There is no significant increase in bleeding in patients who have co-morbidities (p=0.447). In every one unit increase in WBC (1 x 109) the odds of bleeding decrease by 15%. For every one unit increase in hematocrit the odds of bleeding decreases by 6.8%. For every one unit increase in platelet count the odds of bleeding decreases by 3% that is every 10 unit increase in platelet count the odds of bleeding decrease by 22.9%. Conclusions: Female sex, a low initial WBC and platelet count will increase a patient’s propensity to develop bleeding. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, page: 23-28